Age Factors, Parity, Birth Distance Dean Nutritional Status Affects the Incidence of Hyperemesis Gravidarum in Pregnant Women in the First Trimester at the North Tambun Health Center - Suci Saras Wahyuni (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Age at risk < 21 years and > 35 years for first pregnancy, short birth spacing, and nutritional status at risk, namely thin, fat and obese can increase the risk of Hyperemesis Gravidarum. Hormonal changes, differences in body response, and nutritional deficiencies can play a role in the appearance of severe symptoms of nausea and vomiting in Hyperemesis Gravidarum. To determine the factors that age, parity, birth spacing and nutritional status influence the incidence of hyperemesis gravidarum in 1st trimester pregnant women at the Tambun Utara Community Health Center in 2024. The sample size in this study used a total of 58 pregnant women in the 1st trimester based on secondary data from the North Tambun Health Center KIA polyclinic as of January - December 2023 which was taken using total sampling. The analysis method used is univariate and bivariate analysis using the chi square test. There is a relationship between birth spacing and nutritional status with the incidence of hyperemesis gravidarum in 1st trimester pregnant women with a P-value < 0.005. However, there is no relationship between maternal age and parity with the incidence of hyperemesis gravidarum in 1st trimester pregnant women at the Tambun Utara Community Health Center in 2024 with a p value > 0.05. It is hoped that all health workers will pay attention to the health of pregnant women, especially those who experience hyperemesis gravidarum which triggers Hyperemesis Gravidarum incidents in 1st Trimester Pregnant Women, one of which is birth spacing and nutritional status.